مدى مساهمة نظم ذكاء الأعمال في الحد من الاحتراق الوظيفي- دراسة حالة شركة سيريتل (Journal of Hama University, 2025)
The research aims to determine the contribution of business intelligence systems in their dimensions (Competitive Intelligence, Data Exploration, Project Resource Planning System) In reducing functional combustion at Syriatel, the researcher adopted the descriptive approach in an analytical manner by analyzing the data collected through the questionnaire and using the software (SPSS), the community and study sample of all employees of Syriatel Branch Square Al Marj which includes 75/workers and workers, A number of results have been achieved, the most important of which is that the level of competitive intelligence is assessed at a high level according to the views of employees of Syriatel, The level of assessment of data exploration is at a high level according to the views of employees of Syriatel, The level of evaluation of the organization's resource planning systems is also high according to the views of the employees of Syriatel, Also the level of job combustion assessment at a low level according to the views of the employees of Syriatel, There is also a statistically significant contribution to competitive intelligence in reducing functional combustion in Syriatel. There is a statistically significant contribution to the organization's resource planning systems in reducing functional combustion in Syriatel. There is no statistically significant contribution to data exploration in reducing functional combustion in Syriatel and also a statistically significant contribution to competitive intelligence, and the organization's resource planning systems have a greater impact than data exploration in reducing functional combustion. The researcher recommended a number of recommendations, the most important of which is that Syriatel keep abreast of modern technologies to keep abreast of business intelligence developments. Syriatel must provide human development courses for employees and provide a positive organizational climate that limits occupational combustion in all its forms. Syriatel must attract the most skilled and knowledgeable groups in the performance of their mandated tasks by providing them with hooves and the nature of their work, thereby limiting functional combustion.